Risk management in blockchain - AL HOULI, SULTAN (2018)
The aim of the research is to identify the different concepts of blockchain which helps in easier identification of the different risks and the issues associated with blockchain technology. Blockchain is an emerging concept and therefore, it is necessary to identify the different risks and the issues associated with the blockhain technology. The research involves an extensive literature review that aims in thorough understanding of the different concepts and the structure of blockchain architecture. The data collection and data analysis is an important chapter of this research project since it aims in providing an accurate knowledge about the effectiveness of the different risk mitigation approaches that is identified in the literature review section. The research objective is to identify the different risks and the issues associated with a blockchain technology, its system and applications along with the recommendation of the strategy that will help in easier management of the risk and different issues associated with the use of blockchain. It is essential to identify the different risks associated with the use of blockchain and its application and the use and adoption of the blockchain technology is expected to increase in future